Analiza mikrostrukture kompozitov AlSi7-SiC, izdelanih po postopku tiksotropnega ulivanja - Rudolf, Rebeka (Kovine zlitine tehnologije, 1998)
Thixocasting is a novel process where the liquid and the solid phse are vigorously stirred. The normal growing of dendrites is hindered and ?$α$? primary globular crystals evolve. Materials produced in this way are very suited for metal matrix composites. By this procedure one achieves better homogeneity and wettability of reinforcement elements. It was found that a variety of ceramic particulates could be added to the semisolid slurry and kept in suspension without floating and settling. This paper deals with microstructure analysis of composites AlSi7-SiC made by the thixocasting procedure. The results show that the homogeneous distribution of SiC in the matrix depends on the volume fraction of SiC, particle size and morphology of SiC, isothermal stirring time, temperature in the semi-solid and cooling velocity from semi-solid to room temperature. The degree of spheroidization of ?$α_Al$? primary grains is strongly influenced by the peresence of SiC elements.
Keywords: kompoziti; zlitine; aluminij; Aluminij Mostar; aluminum; silicij; mikrostruktura; fazni prehodi